Review: Tsaritsyno: attrakcion s istoriej [Tsaritsyno: An Attraction with History] (Moscow: Novoe literaturnoye obozrenie, 2014), Edited by Natalia Samutina and Boris Stepanov - Максимова, Алиса (Социологическое обозрение, 2014)
Tsaritsyno: attrakcion s istoriej [Tsaritsyno: An Attraction with History] (Moscow: Novoe literaturnoye obozrenie, 2014), Edited by Natalia Samutina and Boris Stepanov